Sini san regulates intestinal flora and short-chain fatty acids to ameliorate hepatocyte apoptosis and relieve CCl4-induced liver fibrosis in mice - Wu, Qiong; Zhu, Fangsi; Yao, Yu; Chen, Luyun; Ding, Yijie; Su, Yong; Ge, Chaoliang (Frontiers in Pharmacology, 2024)
Introduction Si-Ni-San (SNS), a traditional Chinese medicine, is effective in treating liver fibrosis with an unclear mechanism. Although disturbance of intestinal flora and the subsequent secretion of short-chain fatty acids (SCFAs) is suggested to be involved in the progression of liver fibrosis, whether SNS produces the anti-fibrosis effect through the regulation of intestinal flora and SCFAs remains unclear. Methods In the current study, carbon tetrachloride (CCl4)-treated mice were dosed with SNS to examine the anti-fibrotic effects and the involved mechanism. Biochemical parameters, histological staining, and analyses of fibrotic gene expression were used to evaluate the anti-fibrotic effect of SNS, while intestinal flora and SCFA content were determined by 16S rRNA and LC–MS to evaluate the mechanism. Results In vivo results showed that SNS improved liver function, reduced hepatocyte apoptosis and FFAR2/3 expression, and restored intestinal dysbiosis and reduced PA, BA, and IsA levels. In vitro experiments showed that PA, BA, and IsA exacerbated TNF-α-induced HepG2 apoptosis. Notably, the protective effects of SNS were compromised in pseudo-sterile mice. Discussion In conclusion, our experimental results suggest that the disturbance in intestinal flora results in elevated SCFA levels, which further exacerbates hepatocyte apoptosis in liver fibrosis, while SNS suppresses CCl4-induced liver fibrosis at least partially by reinstating intestinal flora homeostasis and reducing SCFA levels.